SLC4A11 and MFSD3 Gene Expression Changes in Deoxynivalenol Treated IPEC-J2 Cells - Xu, Yafei; Chen, Xiaolei; Yu, Luchen; Wang, Yi; Wang, Haifei; Wu, Zhengchang; Wu, Shenglong; Bao, Wenbin (Frontiers in Genetics, 2021)
Deoxynivalenol (DON) caused serious cytotoxicity for animal cells. However, genes involved in regulating DON toxicity and the underlying molecular mechanisms remain largely unknown. This study explored the role of SLC4A11 and MFSD3 in alleviating DON toxicity and analyzed the DNA methylation changes of these two genes. Viability and cell cycle analysis showed that DON exposure decreased the IPEC-J2 viability (P < 0.01), blocked the cell cycle in the G2/M phase (P < 0.01), and increased the rate of apoptosis (P < 0.05). Expression of the SLC4A11 and MFSD3 genes was significantly downregulated upon DON exposure. Overexpression of SLC4A11 and MFSD3 can enhance the cell viability (P < 0.01). DNA methylation assays indicated that promoter methylation of SLC4A11 (mC-1 and mC-23) and MFSD3 (mC-1 and mC-12) were significantly higher compared with those in the controls and correlated negatively with mRNA expression (P < 0.05). Further analysis showed that mC-1 of SLC4A11 and MFSD3 was located in transcription factor binding sites for NF-1 and Sp1. Our findings revealed the novel biological functions of porcine SLC4A11 and MFSD3 genes in regulating the cytotoxic effects induced by DON, and may contribute to the detection of biomarkers and drug targets for predicting and eliminating the potential toxicity of DON.